Developing sociocultural approaches and reconceptualising the play-pedagogy relationship: Malaysian experiences - Norsuhaily, Abu Bakar (2016)
This paper examines contemporary developments in play and pedagogy in early childhood education settings, drawing on Malaysian policies and international play scholarship. Play is also located within contemporary discourses about quality and effectiveness, with a specific focus on “Educational” play (Wood, 2010). Although policy texts and policy-oriented research have provided positive validations for play as integral to ‘effective practice’, there remain significant challenges in conceptualizing the play-pedagogy relationship. The study reported here, explored and analysed some of the challenges inherent to incorporating play into preschool classroom. The research sought to identify any factors that constrain or influence teachers’ implementation of the play approach in four different settings. This paper draws on structured observations, as well as interview data on the perceptions and understandings of teachers, school administrators and parents. A sociocultural theoretical lens was used to interpret observations and to analyze the interview data. Research findings reveal that teachers give more weight to the instrumental value rather than intrinsic value of play. Play serves multiple functions which including recreation function, learning function, developmental function, revelatory function, and class management function in the kindergarten practice. Three main forms of play were found in kindergarten daily routines including play as independent activities, play as components in curriculum, and play as time-fillers. Priority is given to teacher-initiated play rather than children-initiated play.